PENDIDIKAN KARAKTER DALAM PROGRAM SEKOLAHE AREK SURABAYA (SAS) DI SDN SUMUR WELUT III SURABAYA - Indri Nuraini Maulina; Apri Irianto, S.H, M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education is one of the school's efforts to shape students' character. Instilling character education requires a program that can serve as a foundation for instilling character education. Therefore, the Surabaya government initiated a program for schools in Surabaya to instill character education in elementary schools. The purpose of this study is to describe the character values instilled in the Sekolahe Arek Surabaya program at SDN Sumur Welut III. The type of research used by the researcher in this study was descriptive qualitative research. The subjects of this study used interviews, observation, and documentation as data collection techniques. To support the data collection obtained by the researcher, here the researcher used technical triangulation to validate the data obtained from the observations and interviews. The results of this study indicate that character education is instilled through the Sekolahe Arek Surabaya program, covering 18 pillars of character education in the Sekolahe Arek Surabaya program, which are implemented into habits carried out from the beginning of the school day until after the learning process is completed.